Effect of Irrigation, Nitrogen Sources, and Metribuzin on Performance of Maize and Its Weeds - Saudy, Hani Saber; Mohamed El-Metwally, Ibrahim (Communications in Soil Science and Plant Analysis, 2023)
Exploiting water and nutrients by crop plants is limiting by abundance of undesirable plant species viz weeds due to their competitiveness ability, affecting crop productivity and quality. Thus, over two seasons of 2017 and 2018, field experiment was carried out at the Experimental Farm of Faculty of Agriculture, Ain Shams University, Egypt to study the response of maize grain yield and its nutrient constituents and associated weeds to two irrigation intervals (every 15 and 22 days), three weed control treatments (hoeing twice, metribuzin, and unweeded) as well as three nitrogen forms (ammonium nitrate, ammonium sulfate, and urea). The tested factors distributed in a strip plots design with four replications. The results showed that dry weight of grasses (56.1 g m −2 ) and total weeds (67.2 g m −2 ) were lower with irrigation every 15 day. Irrigation every 15 day gave the maximum increase in plant height (233 cm), ear length (18.4 cm), ear diameter (4.7 cm), 100 grain weight (28.0 g), grain yield (7.58 ton ha −1 ) and leaf P (0.29%) and K (2.07%) contents. Hoeing gave the lowest biomass of grasses, total weeds and weeds potassium content, while metribuzin was the superior in diminishing broadleaf weed biomass. Hoeing was as similar as metribuzin as in enhancing plant height, ear length, 100 grain weight and grain yield ton ha -1 . Nitrogen (N) form had no significant effect on weed biomass. However, ammonium nitrate was the most effective form at promoting 100 grain weight, ear length, grain yield ton ha -1 and maize leaf potassium content. Results exhibited that irrigating maize fields every 15 day × hoeing or metribuzin × ammonium sulfate-N could be a combatable and integrative pattern for diminishing weed growth and keeping crop productivity.